2021
DOI: 10.12998/wjcc.v9.i7.1682
|View full text |Cite
|
Sign up to set email alerts
|

Solid pseudopapillary neoplasm-diagnostic approach and post-surgical follow up: Three case reports and review of literature

Abstract: BACKGROUND Solid pseudopapillary neoplasm (SPN) is a rare tumor that was first described by Frantz in 1959. Although this tumor is benign, some may have malignant potential that can be predicted based on demographics, imaging characteristics, and pathologic evaluation. This case series presents 3 SPN cases with discussion on gender differences, preoperative predictors of malignancy, and a suggested algorithm for diagnostic approach as well as post-surgical follow up. CASE SUMMARY … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Some researchers also found that the tumor size for cases with metastases was larger than that of nonmetastatic tumors (8.13 ± 1.03 cm for metastatic tumors and 5.20 ± 3.78 cm for nonmetastatic, range 7-9 cm, P < 0.012). Larger tumor size was significantly associated with the risk of metastasis and recurrence (P < 0.002) (46). The tumor resected from our patient was approximately 20 cm × 20 cm in size, and the postoperative pathological finding of the Ki-67 index was approximately 20%, so we speculated that these clinical features of the patient were one of the possible reasons for the recurrence.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Some researchers also found that the tumor size for cases with metastases was larger than that of nonmetastatic tumors (8.13 ± 1.03 cm for metastatic tumors and 5.20 ± 3.78 cm for nonmetastatic, range 7-9 cm, P < 0.012). Larger tumor size was significantly associated with the risk of metastasis and recurrence (P < 0.002) (46). The tumor resected from our patient was approximately 20 cm × 20 cm in size, and the postoperative pathological finding of the Ki-67 index was approximately 20%, so we speculated that these clinical features of the patient were one of the possible reasons for the recurrence.…”
Section: Discussionmentioning
confidence: 64%
“…Imaging examinations play an important role in the initial diagnosis of SPN, among which the most commonly used imaging modalities are ultrasound, CT, and magnetic resonance imaging (MRI) (17,46). The ultrasound features of SPN are mainly cystic and solid masses with heterogeneous internal echoes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations